Gate threshold voltage instability and on-resistance degradation under reverse current conduction stress on E-mode GaN-HEMTs. (November 2020) - Nakayama, T.; Mannen, T.; Nakajima, A.; Isobe, T.
Abstract: This paper investigates device characteristic shift of E-mode GaN-HEMTs, especially focusing on stress effects under reverse current conduction. Experimental results exhibit that power losses of reverse current conduction is relatively higher than that of forward current conduction. After forward and reverse stress, gate threshold voltages were shifted to negative. On the other hand, on-resistances were increased depending on time duration in the both stress conditions. From our analysis, the electrical parameters shift could be caused by the gate contact and gate electrode degradation. Highlights: This paper investigates device characteristic shift of E-mode GaN-HEMTs, especially focusing on stress effects under reverse current conduction. After forward and reverse stress, gate threshold voltages were shifted to negative. On the other hand, on-resistances were increased depending on stress time duration. From our analysis, the electrical parameters shift could be caused by the gate contact and gate electrode degradation.